Three-dimensional laparoscopic partial cystectomy for intradiverticular bladder carcinoma assisted by articular head linear cutting stapler: A case report and literature review - Yu Gao; Haisheng Yan; Guangyong Li; Peijun Li; Lianghong Ma (Urology Case Reports, 2025)
We present a case of laparoscopic partial cystectomy performed on an 84-year-old Chinese male patient with intradiverticular bladder carcinoma (IDBC). Utilizing the novel method of an articular head linear cutting stapler (AHLCS), we successfully avoided the potential implantation of bladder cancer cells that could have been caused by urine leakage. Postoperative follow-up was conducted using color ultrasound and flexible cystoscopy. The patient's recovery was excellent, with the bladder wound healing well after a follow-up period of 26 months. This case demonstrates that AHLCS-assisted 3D laparoscopic partial cystectomy is a feasible and effective surgical approach for treating intradiverticular bladder carcinoma.